(untitled) (Journal of Monno Medical College, 2025)
Background: A wide variety of medicines are now accessible for asthma treatment and it is important to choose the most favorable treatment. Objective: To evaluate the Drug prescribing pattern of Bronchial Asthma in a Tertiary Level Hospital. Methodology: A cross-sectional type of observational study was carried out over one year in the Department of Pharmacology in collaboration with the Department of Respiratory Medicine and Medicine at Mymensingh Medical College and Hospital, Mymensingh. A total of 160 patients were selected non-randomly for the study. The prescription data from 160 patients with asthma patients were studied using a prescription auditing pro format. Data were recorded from the patients attending the Outpatient Department of Mymensingh Medical College and Hospital. Oral consent was taken from the patients before filling the consent form. Result: During the study, 160 patients were monitored according to their inclusion and exclusion criteria. Demographic analysis of data revealed that there were 73.75% women and 26.25% men in the study. The study showed that maximum patients with asthma belonged to 28-37 years’ age group. Most commonly use single drug is Montelukast that is 6.25% and most commonly used combination therapy is Salmeterol plus Fluticasone, Salbutamol and Montelukast that are 28.13%. Drugs prescribed as monotherapy in this study was Montelukast (6.25%), Methylxanthine (3.13%), Antihistamine (1.88%) and Salbutamol (1.88%). Of these, Montelukast was the preferred drug as monotherapy. Conclusion: The approach to the treatment of Bronchial asthma are vary depend on the severity of the disease. Journal of Monno Medical College December, 2024;10 (2):68-71